Proses Penyelenggaraan Event Musyawarah Nasional Organisasi Profesi Pejabat Pengawas Lingkungan Hidup Tahun 2023 Oleh PT Genesia Dwi Mitra - Astri Amalia Ramadhona; Muhammad Iqbal Katik Rajoendah (Program Studi MICE, Jurusan Administrasi Niaga, Politeknik Negeri Jakarta, 2026)
Environmental pollution and damage are increasing, this condition directly or indirectly disturbs human life. In this case, it is necessary to make comprehensive efforts in the form of effective, consistent, and consistent law enforcement from the Pejabat Pengawas Lingkungan Hidup (PPLH). One of the things that PPLH did to form this professional organization was to hold the first Organisasi Profesi Pejabat Pengawas Lingkungan Hidup National Conference in 2023 online and offline on Wednesday 6 December 2023, appointing PT Genesia Dwi Mitra as the event organizer. This research aims to determine the process of organizing the 2023 Organisasi Profesi Pejabat Pengawas Lingkungan Hidup National Conference. The author uses qualitative methods by collecting data through observation, documentation, and literature study. The findings obtained were that PT Genesia Dwi Mitra had carried out the stages of preparation and implementation of the event properly referring to the terms of reference (ToR) provided by the client.